Sexuality in the Middle Ages and the early modern times : new approaches to a fundamental cultural-historical and literary-anthropological theme - Classen, Albrecht (Fundamentals of medieval and early modern culture ;, 2008)
The studies in this volume explore the phenomenon of sexuality in a variety of medieval and early-modern literatures, including Old English texts, Middle-High German narratives, medieval Spanish and early-modern French literature, and also eighteenth-century English novels. Art historians, historians, and social historians contribute as much as researchers of the history of mentality and religion. The problem with sexuality within the medieval Church finds extensive consideration, and so the fundamental debate among modern sociologists and anthropoligists regarding the evaluation of sexuality,